Safe Oral Antidiabetic Agents in Cardiac Patients: An Update - Haque, SMS; Pathan, F (TAJ: Journal of Teachers Association, 2009)
Cardiovascular disease is the major cause of mortality among patients with type 2 diabetes mellitus, accounting for 60-80% of death in these patients. Despite recent studies demonstrating likely benefit of good glycaemic control in decreasing cardiovascular risk in type 2 DM, there have been lingering concerns about potential adverse cardiovascular effects of insulin secretagogues, specifically sulphonylureas. In this review article, we have tried to explore the issue of safe oral anti-diabetic agents in patients having different cardiovascular diseases. doi: 10.3329/taj.v20i1.3097 TAJ 2007; 20(1): 79-86